Four Human Cases of Acanthotrema felis (Digenea: Heterophyidae) Infection in Korea - Chai, Jong-Yil (The Korean Society for Parasitology and Tropical Medicine, 2014)
Acanthotrema felis is an intestinal trematode of cats originally reported from the Republic of Korea. Only 1 human case infected with a single adult worm has been previously recorded. In the present study, we report 4 human cases infected with a total of 10 worms recovered after anthelmintic treatment and purging. All 4 patients reside in coastal areas of Jeollanam-do, Korea, and have consumed brackish water fish including the gobies, Acanthogobius flavimanus. The worms averaged 0.47 mm in length and 0.27 mm in width, and had 3 sclerites on the ventrogenital sac; 1 was short and thumb-like, another was long and blunt-ended, and the 3rd was long and broad-tipped. They were identified as A. felis Sohn, Han, & Chai, 2003. Surveys on coastal areas to detect further human cases infected with A. felis are required.